The Effects of an Acceptance and Commitment-Informed Interdisciplinary Rehabilitation Program for Chronic Airway Diseases on Health Status and Psychological Symptoms - Giusti, Emanuele Maria; Papazian, Barbara; Manna, Chiara; Giussani, Valentina; Perotti, Milena; Castelli, Francesca; Battaglia, Silvia; Galli, Pietro; Rossi, Agnese; Re, Valentina; Goulene, Karine; Castelnuovo, Gianluca; et al. (Frontiers in Psychology, 2022)
Background: Chronic airway diseases are prevalent and costly conditions. Interdisciplinary rehabilitation programs that include Acceptance and Commitment-based (ACT) components could be important to tackle the vicious circle linking progression of the disease, inactivity, and psychopathological symptoms. Methods: A retrospective evaluation of routinely collected data of an interdisciplinary rehabilitation program was performed. The program included group sessions including patient education, breathing exercise, occupational therapy and an ACT-based psychological treatment, and individual sessions of physical therapy. Demographic data, clinical characteristics of the patients and the values of outcome variables (health status, quality of life, anxiety, and depression) before treatment, at discharge, at three months, and at six months were extracted from medical records. Multiple imputation was employed to address missing data. Linear mixed models were employed to assess changes over time. Multivariable logistic regression was performed to assess predictors of a minimum clinically important change of health status from baseline to the 6-months follow-up. Results: Data from 31 patients with COPD and 12 patients with bronchiectasis were extracted. Health status improved from baseline to discharge to the three months follow-up, but not to the six months follow-up. Anxiety and depression improved across all the time points. Quality of life did not improve over time. Having a worse health status at baseline and fewer depressive symptoms were significantly associated with achieving a minimum clinically important change of health status at six months. The effects of the interdisciplinary program were not different for patients with COPD or with bronchiectasis. Discussion: Interdisciplinary programs including ACT-based components are promising treatments for the rehabilitation of patients with chronic airway diseases.